2015
DOI: 10.18433/j3fg7g
|View full text |Cite
|
Sign up to set email alerts
|

The Lidose Hard Capsule Formulation of Fenofibrate is Suprabioavailable Compared to the Nanoparticle Tablet Formulation Under High-fat Fed Conditions

Abstract: -Purpose:The therapeutic equivalence of multiple registered fenofibrate formulations, several of which are suprabioavailable and therefore marketed at lower dosage strengths than their reference products, is based on the results of bioequivalence studies. Most of these formulations show a higher bioavailability when taken with a high-fat meal. The relative bioavailability of two of these formulations, the 200 mg Lidose hard capsules and the 145 mg nanoparticle tablets, was assessed when taken with a high-fat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…On the other hand, fenofibrate is on the market as the LBF Fenogal. Fenogal contains homogeneously dispersed fenofibrate (200 mg) within a lipid excipient mixture (Gelucire 44/14) and can be classified as a class IIIb formulation according to the Lipid Formulation Classification System (LFCS) [6]. Gelucire 44/14 is a semi-solid self-emulsifying lipid excipient, composed of C8-C18 MAGs, DAGs and TAGs (solubilisation), C8-C18 mono-and diesters of PEG-32 (surfactants) and free PEG-32 (co-solvent), which forms a finely dispersed microemulsion when in contact with the aqueous environment of the GI tract [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, fenofibrate is on the market as the LBF Fenogal. Fenogal contains homogeneously dispersed fenofibrate (200 mg) within a lipid excipient mixture (Gelucire 44/14) and can be classified as a class IIIb formulation according to the Lipid Formulation Classification System (LFCS) [6]. Gelucire 44/14 is a semi-solid self-emulsifying lipid excipient, composed of C8-C18 MAGs, DAGs and TAGs (solubilisation), C8-C18 mono-and diesters of PEG-32 (surfactants) and free PEG-32 (co-solvent), which forms a finely dispersed microemulsion when in contact with the aqueous environment of the GI tract [7].…”
Section: Introductionmentioning
confidence: 99%
“…Gelucire 44/14 is a semi-solid self-emulsifying lipid excipient, composed of C8-C18 MAGs, DAGs and TAGs (solubilisation), C8-C18 mono-and diesters of PEG-32 (surfactants) and free PEG-32 (co-solvent), which forms a finely dispersed microemulsion when in contact with the aqueous environment of the GI tract [7]. Although elimination of a food effect can be observed in vivo for some compounds formulated as LBFs [8][9][10], Fenogal still needs to be taken with a meal to enhance the oral bioavailability of fenofibrate [6]. In theory, both acylglycerols and PEG esters are substrates for digestive enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Это позволяет снизить суточные и курсовые дозы изотретиноина LIDOSE на 20%: рекомендованный диапазон суточных доз CИ, произведенного по технологии LIDOSE, составляет 0,4-0,8 мг/кг, курсовых доз -100-120 мг/кг. Уменьшение разовой и курсовой дозировки изотретиноина на 20% с полным сохранением терапевтической эффективности обусловливает уменьшение числа побочных эффектов [48,49]. Изотретиноин плохо растворим в воде, поэтому всасывание препарата происходит лучше при его приеме с пищей.…”
Section: выбор лекарственной формы изотретиноинаunclassified
“…Recent bench studies have demonstrated an array of cardiovascular and renal pleiotropic beneficial activities of fenofibrate, besides its foremost lipid-lowering action [1,2]. There are many available formulations of fenofibrate on the market, such as micronized capsules and tablets, nanocrystal tablets, and fenofibric acid (FA) capsules (delayed-release) [3][4][5]. The pharmacokinetic studies of these preparations have been conducted in many countries, however, the pharmacokinetic studies of fenofibrate tablets (Lipanthyl ® supra, 160 mg) in Chinese subjects have not been reported.…”
Section: Introductionmentioning
confidence: 99%